Cyclin D1 expression of different histological grades in oral squamous cell carcinoma patients from northern India - Gatoo, Manzoor Ahmad; Dar, Ayaz Mahmood (Archive of Oncology, 2018)
Cyclin D1 expression was positive in 35 cases of oral cancer with a Cyclin D1 positivity of 22.16±22.18. The percentage of positive cases as well as Cyclin D1 positivity showed an increase as the grade of differentiation advanced. No significant association was found between Cyclin D1 positivity and degree of differentiation of tumors (p=0.138). A significant difference in Cyclin D1 positivity was observed (p=0.043) comparing well differentiated (16.61+17.89) and poorly differentiated (37.0±32.51) tumors, as well as between well differentiated (16.61+17.89) and moderately differentiate tumors (24.38+21.93; p=0.002). Similarly, significant difference in Cyclin D1 positivity was observed comparing moderately differentiated (24.38+21.93) and poorly differentiated tumors (37.0±32.51; p =0.043). Cyclin D1 expression was more frequently seen in hard palate (75%), buccal mucosa (67 %) and lip (60 %) while expression of Cyclin D1 was less frequent in sites like gingiva (0 %), tongue (40 %) and floor of mouth (43 %). There was no association between Cyclin D1 expression and primary site of oral cancer (p=0.528) in tobacco and betel quid chewers of northern India.
Keywords: oral carcinoma; Northern India; betel quid chewers; Cyclin D1